Studies to enhance the shelf life of tomato using aloe vera and neem based herbal coating - Kumar, Jaiswal Alok; Simple, Kumar; Tripti, Bhatnagar (Journal of Postharvest Technology, 2018)
The present study was carried out to evaluate the ability of Aloe gel based herbal coatings to reduce the loss of post harvest quality in Tomato  (Solanum lycopersicum L.). Unripe green to reddish Tomato fruits were coated with different formulations of Aloe vera gel, Neem extract,  Salicylic acid and citric acid. The coated and uncoated fruits were stored under different physiological conditions to slow down the ripening  process. Visual, Firmness and sensory characteristics and marketability were analyzed at regular intervals during the storage period. It was  found that the coatings controlled the physiological loss in weigh (PLW), ripening process and decay to a great extent and thus resulted in  extended shelf life and better quality of Tomatoes. The effectiveness of Aloe vera gel coating was found to improve on incorporation of citric  acid and neem extract.
Keywords: Aloe vera; edible coating; shelf life; tomato; neem extract.